The Influence of Social Media and Digital Literacy on Students' Learning Achievement in Economics Subjects - Amalia, Ayu Nurul; Supriyadi, Supriyadi (IJBLE Scientific Publications Community Inc., 2023)
The world of technology is developing very rapidly over time and has become a need for every human being. The research aims to reveal the influence of social media and digital literacy on students' learning achievement in economics subjects. The research uses quantitative methods with a survey approach. The population of all class Data was obtained from valid and reliable instruments. Data analysis uses partial and multiple regression. The research results concluded: 1) Social Media has a positive effect on students' learning achievement in Economics Subjects; 2) Digital Literacy does not have a positive effect on students' learning achievement in economics subjects; 3) There is a joint (simultaneous) influence of Social Media and Digital Literacy on students' learning achievement in economics subjects; 4) The influence of social media and digital literacy together on learning achievement in economics subjects is 80.4%; 5) The correlation between Social Media and learning achievement in Economics subjects by controlling the Digital Literacy variable is significant; 6) the correlation between Digital Literacy and learning achievement in economics subjects by controlling social media variables is not significant.